PENERAPAN UPAYA DAMAI OLEH PIHAK KEPOLISIAN DALAM PENYELESAIAN PERKARA TINDAK PIDANA DI WILAYAH KEPOLISIAN SEKTOR LIMA PULUH KOTA PEKANBARU - Novem S Hutauruk; Mukhlis R; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
In the Indonesian criminal law is not known peace efforts, but the reality on the ground often occurs through a peace settlement that criminal investigation of a criminal case can be stopped. Based on this fact, there are three formulation of the problem in writing this essay, namely: How does the application of the First peace efforts by the police against criminal assault on Police Jurisdiction Lima puluh Pekanbaru?, Both juridical What are the constraints faced by the police in the implementation effort peace by the police against criminal assault on police jurisdiction Lima puluh Pekanbaru?, third, How the efforts made by the police in overcoming obstacles in the application of the juridical peace efforts by the police against criminal assault on police jurisdiction Lima puluh Pekanbaru?The research method in this study is a qualitative research method with empirical juridical or legal sociological research. Data sources supported by primary and secondary data sources. Data collection techniques used were interviews and review of literature. After the data collected was then analyzed qualitatively, and draw conclusions with deductive thinking method is to analyze the problems of the general form to a specific shape.From the results of research and discussion, it can be concluded that, Mechanisms for resolving criminal cases through peaceful means or through some process steps, namely, receipt of the report, calling witnesses, the case and the application of article titles, peace between the complainant and reported his case for peace efforts, decision of whether or not the legitimate leader of the peace efforts, create a dossier reporting witness back reporting witness back, revocation reports, and the reporting and photo reported and witnesses as well as the signing of the peace. The juridical obstacles in its implementation, namely the lack of rules in the legislation governing the implementation of the peace efforts by investigators in the completion of a criminal offense, status and nature of the Indonesian Penal Code as a public law that requires completion of a criminal case through the criminal justice system there, setting the implementation of police discretion contained in the Act does not provide a detailed and clear explanation of how the procedures of police discretion and the limits of the implementation of police discretion and laws that have multi language interpretation. Then made several attempts to overcome these obstacles by promoting juridical norms and customary habits in society, upholding the principles of restorative justice, the possibilities were proposed legislation changes both the Criminal Code and the Law on Police, as well as enhancing the ability of the police in the understanding of the legislation in force.